VASCULAR ENDOTHELIAL GROWTH FACTOR AND HLA-PHENOTYPE IN PATIENTS WITH CHRONIC GLOMERULONEPHRITIS - KolesnykМ.; Driyanska, V.; VelychkoМ.; Drannik, G.; Nepomnyaschiy, V.; Savchenko, V.; Gaiseniuk, F. (Ukrainian Journal of Nephrology and Dialysis, 2016)
It was to determine associations the serum levels ofVEGF and with HLA inpatients with chronic glomerulonephritis and nephrotic syndrome (CGN, NS). Materials and methods. There was studied the serum levels of VEGF (80 patients) by ELIZA and HLA-antigens distribution in the CGN, NS patients (534) by typing the lymphocytes with the aid of standard microlymphocytotoxic test (Terasaki’s test). The diagnosis was confirmed morphologically using by nephrobiopsy. Results. The distribution of HLA-A, В antigens of the 2 group patients having the CGN, NS with various serum levels of VEGF is shown. Associations of some HLA-antigens and high levels of vascular endothelial growth factor in blood were noted. Conclusion. High serum level VEGF and HLA-A9, A10 (25+26) and B8 in CGN, NS patients associated with steroidoresistence.